ANALISIS KARAKTERISTIK HUBUNGAN INSEMINATOR TERHADAP KEBERHASILAN INSEMINASI BUATAN (IB) TERNAK SAPI DI KOTA SAWAHLUNTO - Aprisal; Jaswandi Jaswandi; Tinda Afriani (Wahana Peternakan, 2023)
ABSTRACT The purpose of this study was to identify the relationship between inseminator characteristics (internal and external) to the success of AI in Sawahlunto City. The objects of this research observation are all inseminators in Sawahlunto City. The data were analyzed with the simultaneous F test to see the effect of the variables simultaneously and the Partial T Test to see the effect of each variable. The results of the study found that the success of artificial insemination in Sawahlunto City was not very good, where an average S/C value of 3.04 was found. Internal characteristics (years of service, thoroughness, responsibility, technical ability in straw and thawing management, ability to understand the anatomy of the reproductive organs) and external (distance from home to work area, completeness of facilities and infrastructure, sanitation of equipment, communication of livestock reporting) have a significant relationship (P<0.05) on AI success, while internal (experience, training intensity) and external characteristics (IB postal conditions) did not have a significant relationship (P>0.05) to AI success in Sawahlunto City. From the results of this study it can be concluded that the characteristics of the inseminator (external and internal) influence the success of AI in Sawahlunto City. Keywords: Artificial Insemination (AI); Inseminator; Internal and Eksternal Characteristics